2021
DOI: 10.6007/ijarbss/v11-i7/10039
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Vocabulary Learning Strategies among Form 6 Students in a Malaysian Private School

Abstract: There are varieties of vocabulary learning strategies that can be implemented by all students. According to various past studies, vocabulary learning strategy is one of the learning methods that benefit pupils' learning style and method inside and outside of the classroom. The findings of past studies indicate that vocabulary learning strategies improve students' understanding in mastering a topic and this is also applied with learning vocabulary. Thus, the aim of this study is to investigate the vocabulary le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As such, they would avoid using rehearsal strategies. Besides that, Sasidaran et al (2021) found that most secondary students did not prefer to use the encoding strategy as their teachers did not incorporate the strategies in their learning process.…”
Section: Research In Vls Among Secondary School Studentsmentioning
confidence: 99%
See 3 more Smart Citations
“…As such, they would avoid using rehearsal strategies. Besides that, Sasidaran et al (2021) found that most secondary students did not prefer to use the encoding strategy as their teachers did not incorporate the strategies in their learning process.…”
Section: Research In Vls Among Secondary School Studentsmentioning
confidence: 99%
“…In addition, Sasidaran et al (2021) examined VLS employed by 50 secondary school students in Selangor, Malaysia. The study used VLSQ version 6.4, adapted from Gu (2018), as their principal instrument.…”
Section: Research In Vls Among Secondary School Studentsmentioning
confidence: 99%
See 2 more Smart Citations